Phylogenetic relationships and sectional delineation within Gentiana (Gentianaceae). Issue 6 (29th November 2020) - Favre, Adrien; Pringle, James S.; Heckenhauer, Jacqueline; Kozuharova, Ekaterina; Gao, Qingbo; Lemmon, Emily Moriarty; Lemmon, Alan R.; Sun, Hang; Tkach, Natalia; Gebauer, Sebastian; Sun, Shan‐Shan; Fu, Peng‐Cheng
Abstract: Gentiana is a sub‐cosmopolitan temperate genus among the most species‐rich in Gentianaceae. Although molecular data (produced via Sanger sequencing) allowed the resolution of phylogenetic relationships between Gentiana and other genera in subtribe Gentianinae, the validity of sections within the genus remains largely untested. In this study, we evaluated the monophyly of all 14 sections attributed to Gentiana, using 294 unlinked anchored loci, the nuclear ribosomal DNA (rDNA) cistron as well as plastid genomes, all produced by anchored hybrid enrichment. We reconstructed phylogenetic relationships by conducting maximum likelihood and Bayesian analyses. These analyses represent a significant improvement over previous taxonomic studies using molecular tools. Our results partly correspond to traditional taxonomic treatments, with several sections being well supported as monophyletic, including Gentiana sect. Calathianae, sect. Ciminalis, sect. Cruciata, sect. Frigida, sect. Gentiana and sect. Pneumonanthe . In contrast, G. sect. Isomeria, sect. Microsperma and sect. Monopodiae were found to be polyphyletic, whereas sect. Dolichocarpa and sect. Fimbricorona were nested within sect. Chondrophyllae . We here provide new taxonomic treatments for these sections, mostly based upon the traditional delineation of their series, which were recovered as monophyletic. In our new treatment, Gentiana encompasses 13 sections. A new determination key to the sections of Gentiana is provided.